Recreational use of forests by young people - Cichowska, Jolanta (Leśne Prace Badawcze, 2020)
The article is a continuation of research conducted in 2016–2017, whose goal was to determine expectations and needs of young people regarding forests. In this study, attention is focused on different preferences of high-school students and University students. Frequency and reasons for which high-school students visit forests have been studied. Forms of forest activities preferred by the respondents as well as familiarity of young people with the sanitary state of the woodlands, the role of biocoenosis in the ecosystem and its significance for people have been analysed. The respondents’ knowledge of rules to be followed when being in a forest, use of its resources and major threats to this ecosystem have been studied.